2003
DOI: 10.1179/135100003125001288
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of protein hydroperoxide formation by protein thiols

Abstract: Studies on plasma and cells exposed to hydroxyl and peroxyl radicals have indicated that there are few inhibitors of protein hydroperoxide formation. We have, however, observed a small variable lag period during bovine serum albumin (BSA) oxidation by 2-2' azo-bis-(2-methyl-propionamidine) HCl (AAPH) generated peroxyl radicals, where no protein hydroperoxide was formed. The addition of free cysteine to BSA during AAPH oxidation also produced a lag phase suggesting protein thiols could inhibit protein hydropero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…Studies on SOD activity in patients with SLE have been inconsistent. Most studies showed that SOD activity was decreased in patients with SLE, 3,15 but other studies showed that it was increased or unchanged 20 . The reported decreased GSH‐Px and catalase activity in serum, plasma, red blood cells and whole blood in patients with SLE 21 are in agreement with our findings, but unaltered catalase activity in plasma and serum has also been reported 4,21 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Studies on SOD activity in patients with SLE have been inconsistent. Most studies showed that SOD activity was decreased in patients with SLE, 3,15 but other studies showed that it was increased or unchanged 20 . The reported decreased GSH‐Px and catalase activity in serum, plasma, red blood cells and whole blood in patients with SLE 21 are in agreement with our findings, but unaltered catalase activity in plasma and serum has also been reported 4,21 .…”
Section: Discussionsupporting
confidence: 91%
“…Another significant consequence of free‐radical damage to proteins is the formation of protein hydroperoxides. Protein thiol groups can inhibit protein hydroperoxide formation by scavenging peroxyl radicals 3 . Their measurement in serum provides an indirect reflection of protein oxidation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also particularly compelling evidence to suggest the participation of vicinal pyrimidine peroxyl radicals in the formation of 8-oxo-dG (Bergeron et al, 2010; Douki et al, 2002). Further, it should be noted that peroxyl radicals are much longer-lived than hydroxyl radicals (Lim et al, 2004; Simandan et al, 1998) and hence 8-oxo-guanine formation elicited by antibiotics could potentially be affected by the presence of antioxidants such as glutathione that react with peroxyl radicals (Platt and Gieseg, 2003). …”
Section: Resultsmentioning
confidence: 99%
“…Generally, it can be assumed that the same reactions, which in protein-lipid food products cause a reduction in the nutritional value or quality due to the modifi cation of the protein fraction, determine the protective effect of peptides on the lipid fraction in the protein-stabilized emulsion model systems and depending on the reference system, these changes are determined as either negative or positive. The antioxidant activity of proteins can be considered at three levels: the properties of proteins as polymers of amphiphilic structure, that is hydrophobic-hydrophilic, which determines, among other aspects, the surfactant activity of these compounds [Viljanen, 2005]; antioxidant activity of individual amino acids [Saito et al, 2003;Platt & Gieseg, 2003;Levine et al, 1996]; and the antioxidant nature of colored macromolecular compounds, which are products of non--enzymatic browning as a result of the interaction of oxidized lipids and proteins [Alaiz et al, 1996. Macromolecular compounds formed as a result of condensation between secondary lipid oxidation products and proteins exhibit moderate antioxidant activity [Chelh et al, 2007].…”
Section: The Technological Value Of Proteinsmentioning
confidence: 99%